Empirical modeling and optimization of kerf width in abrasive water jet machining – a short review - Subbaiah, K. Venkata; Baburaja, Kammuluri (International Journal of Engineering and Technology, 2018)
Changing demands of the industries require advanced materials to meet the demands of the industries researchers are constantly creating newer materials such as alloys, metal matrix composites and hybrid materials these metal materials are tailored either ferrous or non-ferrous, due to different compositions material properties are altered with respect to physical and mechanical properties, some of them are malleabil-ity, ductility, hardness and toughness, to machine these materials conventional methods of machining using lathe, milling, drilling may not be suitable due to low productivity and poor in accuracy and surface finish because of the boosted material properties. A capable method of machining would be unconventional machining methods such as wire EDM, Laser beam machining, chemical machining, electro chemical machining, water jet machining and abrasive water jet machining. In this paper the implication of abrasive water jet machining is emphasized based on the valuable research carried out by various researchers across the globe. This paper put forward the materials used, parameters considered, and design of experiments emphasized by researchers.